Adsorption of CO2 on MIL-53(Al): FTIR evidence of the formation of dimeric CO2 species. Issue 7 (10th December 2015) - Mihaylov, M.; Chakarova, K.; Andonova, S.; Drenchev, N.; Ivanova, E.; Pidko, E. A.; Sabetghadam, A.; Seoane, B.; Gascon, J.; Kapteijn, F.; Hadjiivanov, K.
Abstract : FTIR spectra of 12 CO2 and 12 CO2 + 13 CO2 mixtures adsorbed on MIL-53(Al) reveal the formation of highly symmetric dimeric (CO2 )2 species connected to two structural OH groups. Abstract : FTIR spectra of 12 CO2 and 12 CO2 + 13 CO2 mixtures adsorbed on MIL-53(Al) reveal the formation of highly symmetric dimeric (CO2 )2 species connected to two structural OH groups.